Vitality of Tae' Language in Palopo, South Sulawesi - Rusdiansyah, Rusdiansyah; Kurniawan, Eri; Malik, Fidia Ditazam (Institut Agama Islam Negeri Palopo, 2023)
This study discusses the vitality of the Tae’ language in Palopo city, South Sulawesi. Vitality of Tae’ language can be seen both from its use as a language of daily communication, the number of speakers, documentation, government policies related to the language, and the inclusion of the language in the school curriculum. The method used in this study is a qualitative descriptive method, in which interviews and observations were employed. The subjects interviewed were government officials in Palopo city, as well as the people of Palopo. Findings reveal that the vitality of the Tae language in Palopo is vulnerable to extinction. This is characterized by two main indicators: i) very low use of Tae’ language even in the family domain which affects low language transmission as well ;) and the absence of govermental policies in preserving and maintaining Tae’ language as the identity of the Palopo people and the Indonesian.